Evolution of large-scale magnetic fields in the Sun - Brayko, P.G. (Кинематика и физика небесных тел, 2005)
A scenario of evolution of the large-scale magnetic fields in the Sun is proposed. The analysed models of the Sun allow one to accept the shearing of the poloidal field by differential rotation, helical turbulence and also the advective transport of the magnetic flux by meridional circulation as the main processes of the solar activity. We found that toroidal magnetic field (TMF) was more effectively generated in the strong radial shear layer (tachocline). It has a small value of diffusion and is carried out by meridional circulation toward the equator, where diffusion of the fields with different signs takes place. Casual force takes away the partial TMF in the solar convective zone and magnetic buoyancy sends the field to the surface. Using the Babcock–Leighton idea, we give confirmation of the generation of the poloidal magnetic field only near the surface and poles. The approximate decisions enable one to build the model of the solar dynamo in accordance with the observations.